Photocatalytic activity of π-conjugated conducting polymer microspheres from ultrasonic spray pyrolysis. (June 2017) - Liu, Yangshuo; Li, Ming; He, Chiyang
Conductive polymers have considerable interest on degradation of pollutants from textile wastewaters and appear as a new class of active photocatalysts under visible light. Poly(3, 4-ethylenedioxythiophene) (PEDOT), as one of π-conjugated conducting polymer microspheres, is highly efficient catalyst in textile pollutant degradation. Ultrasonic spray pyrolysis method was used to produce spherical PEDOT particles in one step. The novel PEDOT-based photocatalysts are very stable with cycling and can be reused without appreciable loss of activity. Ag–ZnO nanocatalysts are not effective photocatalysts as compared to highly porous microspheres of PEDOT. After 240 min total processing time for the solution of phenol and RR180 under Vis irradiation, the performances of 71.6% and 78.2% for degradation and 68.3% for total organic carbon removal of RR180 were reached in the presence of the porous PEDOT photocatalysts.